Cohesion as a choice : regardless of faith and identity - Jerard, Jolene (2021)
Social cohesion is a work in progress. Societies can choose to achieve greater levels of social cohesion by forging greater inclusivity. Two things can break this: Exclusivist ideas and the imposition of perceived group superiority.